Synchronous Modification Design for Bilateral Tooth Surface of Spiral Bevel Gear by Dual Duplex Spread Blade Method - Jianjun Yang; Xinfang Hu; Hua Zhang; Shaowu Nie (Jixie chuandong)
Aiming at the dual duplex spread blade method for cutting spiral bevel gears, the midpoint of the tooth space of pinion is treated as the reference point for the bilateral modification tooth surfaces. The target tooth surface is constructed to meet with the meshing performance by predetermining of the meshing parameters. The mathematical model and constraint function of the target tooth surface errors based on the optimization of machining tool setting are constructed. The nonlinear constrained optimization function is used to derive the machining parameters of the gear. The optimized method is verified by tooth contact analysis and finite element contact analysis. The simulation results show that the meshing performance meets the expected requirements after the tooth surface modification.